Children's active outdoor play: 'good' mothering and the organisation of children's free time. Issue 6 (30th May 2020) - Clark, Emily; Dumas, Alex
Abstract: This qualitative study draws on the Foucault‐inspired notion of biopedagogies to examine and problematise the salient factors of contemporary motherhood impacting children's active outdoor play (AOP). The study positions mothering as a practice, through which children's health and bodies are constructed and disciplined. A discourse analysis of 21 interviews with Canadian mothers identified three discursive constructions of the 'good mother': mothers as time managers, risk managers and screen‐time managers. Each was characterised by discursive conflicts that compromised the provision of AOP by mothers. This study provides data necessary for successfully including AOP as a leisure practice within family‐centred health promotion.